Relationship between Environmental Conditions and Distribution of 10 Most Common Diseases in the Lubuk Alung Health Center Work Area in 2024 - Fitri Sadilla; Indang Dewata; Nurhasan Syah; Mulya Gusman; Iswandi Umar; Mery Delvina (Postgraduate, University of Mataram, 2025)
Public health reflects a complex and dynamic interaction between various determinants, where environmental conditions play a crucial role in influencing disease distribution patterns. The type of research used is qualitative through a descriptive approach. Data from this study were collected through medical records of patients visiting the Lubuk Alung Health Center during the period January to December 2024. The data collection process was carried out by health center officers by accessing medical records to document the type of disease and the number of cases based on their respective work areas. Furthermore, each case of disease was classified according to the type of disease and the patient's area of ​​residence. This study was conducted in the work area of ​​the Lubuk Alung Health Center, Padang Pariaman Regency, West Sumatra. The results of this study found that the distribution of the ten most common diseases was greatly influenced by local environmental conditions in seven villages, namely Air Tajun, Balah Hilir, Lubuk Alung, Pasir Lawas, Pangkalan Kasiak, Sei Abang, and Singguling. The disease with the highest number of cases was ARI (393 cases), followed by Diabetes Mellitus (355 cases), Hypertension (196 cases), Schizophrenia (168 cases), Dyspepsia (135 cases), Cephalgia (35 cases), Febris (56 cases), Skin Disease (45 cases), Heart Disease/HT (50 cases), and Other Diseases (51 cases). Balah Hilir and Pangkalan Kasiak villages showed the highest prevalence of diseases in general, with Balah Hilir recording the highest cases of ARI (97), Diabetes Mellitus (63), Dyspepsia (30), and Heart Disease/HT (11), while Pangkalan Kasiak dominated cases of Diabetes Mellitus (79), ARI (85), and Hypertension (65). Sei Abang also had high figures for ARI (67), Schizophrenia (17), and Skin Disease (12). In contrast, villages such as Pasir Lawas and Lubuk Alung had relatively lower cases of most diseases. This uneven distribution of disease indicates the strong influence of local environmental factors such as air quality, sanitation, lifestyle, and health infrastructure, so that specific area-based interventions are needed to improve overall public health.